Salmonella osteomyelitis in a renal transplant recipient. Brief report - Wong, Arturo; García, Rafael; Henriquez, Carlos; Rodríguez Iturbe, Bernardo (Investigación Clínica, 2013)
This report concerns a renal transplant recipient who developed osteomyelitis due to Salmonella enteritidis serotype Dublin. The patient is a 43-year aold man with chronic renal failure due to nephrosclerosis, who developed unexplained fever one month after receiving a kidney from his father. Salmonella Dublin, was isolated from 3 blood cultures. He responded well to oral chloramphenicol therapy which was maintained for 4 weeks. He remained asymptomatic for 1 month. At this time lie again presented fever fever and radiolucent bone lesion was found in the tibia. Salmonella Dublin was cultured from the blood, as well as from the bone lesion. The patient responded well to surgical treatment of the osteomyelitis and therapy with ampicillin and trimetroprimsulphamethoxazole which was maintained for 3 months. It is suggested that salmonella infections require prolonged treatment in inmunosuppressed patients and that it may be advisable to investigate the carrier state in transplant candidates in geographical areas where salmonellosis is endemic.